2015
DOI: 10.1111/ajt.13147
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Intestinal Transplant Listing Criteria – A Call for a Change in the New Era of Intestinal Failure Outcomes

Abstract: Current listing indications used for intestinal transplantation (IT) were proposed in 2001. We undertook the present single center study to see if these criteria are still valid. The 2001 criteria (advanced cholestasis, loss of >50% central venous catheter (CVC) sites, !2 sepsis/year, ultrashort bowel) were compared in children with intestinal failure in old era-1998-2005 (N ¼ 99) to current era-2006-2012 (N ¼ 91) to predict the need for IT using sensitivity, specificity, NPV and PPV. Two 2001 criteria had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…In a single center study evaluating pediatric patients treated in a modern era, historical listing criteria were no longer predictive of mortality or need for transplantation. (67) In this study, cholestasis was only predictive if a patient failed 6 weeks of liver sparing lipid strategies. If validated in a larger study, this data will likely continue to contribute to the changing role of transplantation for the patient with IF.…”
Section: Evolving Indications For Intestine Transplantationmentioning
confidence: 68%
“…In a single center study evaluating pediatric patients treated in a modern era, historical listing criteria were no longer predictive of mortality or need for transplantation. (67) In this study, cholestasis was only predictive if a patient failed 6 weeks of liver sparing lipid strategies. If validated in a larger study, this data will likely continue to contribute to the changing role of transplantation for the patient with IF.…”
Section: Evolving Indications For Intestine Transplantationmentioning
confidence: 68%
“…However, with the likelihood of survival on home PN approaching 90% at 5 years, exceeding that of intestinal transplantation (60%), there has been a proposal to remove the diagnosis of USBS as an indication for bowel transplantation. 30 A recent publication by Burghardt et al found that in the old era of increased mortality, the diagnosis of USBS was previously strongly predictive of requiring an intestinal transplant (positive predictive value = 100%), but in the current era of improved survival, USBS diagnosis had a decreased positive predictive value of 9%. 30…”
Section: Transplantationmentioning
confidence: 99%
“…While neonates were traditionally at greatest risk of death from IFALD, recent advances in parenteral lipid formulations have markedly improved outcomes . Evidence is emerging that use of soybean oil (SO) promotes IFALD, while lipid emulsions containing fish oil (FO) may prevent and can treat IFALD.…”
Section: Introductionmentioning
confidence: 99%
“…While neonates were traditionally at greatest risk of death from IFALD, recent advances in parenteral lipid formulations have markedly improved outcomes. 2 Evidence is emerging that use of soybean oil (SO) promotes IFALD, 3 while lipid emulsions containing fish oil (FO) may prevent 4 and can treat 5,6 IFALD. Possible reasons for improved outcomes with FO-containing lipid emulsions can be related to compositional differences, including added vitamin E, lower amounts or absence of phytosterols, and key differences in fatty acid composition, including the presence of eicosapentaenoic acid and docosahexaenoic acid in FO.…”
Section: Introductionmentioning
confidence: 99%